Corruption and development, revisited - Jenny D. Balboa; Shinji Takenaka (Philippine Institute for Development Studies (PIDS), 2010)
Graft and corruption is considered to be one of the biggest threats to development. Several studies had shown the tremendous impact of corruption in the economy. For a number of developing countries, a huge portion of government resources is lost and wasted due to corrupt activities, further plunging the country to poverty and underdevelopment. Various efforts to combat this social ill have been explored. However, the problem continues to persist. This short paper revisits the issue and aims to contribute to the growing literature of understanding corruption in developing economies and creating the necessary policy response. It answers the following questions: What are the different forms of corruption? What drives corruption? What has been done to address the issue? The Philippine case is also briefly discussed.
Keywords: O19; O5; F5; 330; political economy; corruption; development; Korruption; Entwicklung; Anti-Korruption; Entwicklungsländer